2021
DOI: 10.1108/jaee-02-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of corporate environmental disclosures in Sri Lanka: the role of corporate governance

Abstract: PurposeThis study explores the levels of and trends in corporate environmental disclosure (CED) among a sample of Sri Lankan listed companies from 2015 to 2019. Furthermore, this article examines the firm-level determinants of CED, including corporate governance (CG) mechanisms, in Sri Lanka from a multi-theoretical perspective.Design/methodology/approachUsing a sample of 205 firm-year observations, this paper distinctively applies a panel quantile regression (PQR) model to examine the determinants of CED in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 123 publications
(319 reference statements)
7
59
0
Order By: Relevance
“…This was also found to be significant by Farber (2005), whilst Owens-Jackson et al (2009) provided weak evidence of this in similar studies. This comes as no surprise, as larger audit firms are argued to give higher quality audits (Astami et al , 2017; BenYoussef and Drira, 2020; Bhuiyan and D’Costa, 2020; Chan et al , 2020; Elamer, 2019b, 2019a; El-Dyasty and Elamer, 2021; Eshleman and Guo, 2014; Gerged et al , 2020; Ji et al , 2015; Nuskiya et al , 2021; Owusu et al , 2020; Zeng et al , 2020). Further to this, Sundgren and Svanstrom (2012) argue smaller audit firms receive more sanctions due to poorer audit quality, which coincides with the results above.…”
Section: Resultsmentioning
confidence: 99%
“…This was also found to be significant by Farber (2005), whilst Owens-Jackson et al (2009) provided weak evidence of this in similar studies. This comes as no surprise, as larger audit firms are argued to give higher quality audits (Astami et al , 2017; BenYoussef and Drira, 2020; Bhuiyan and D’Costa, 2020; Chan et al , 2020; Elamer, 2019b, 2019a; El-Dyasty and Elamer, 2021; Eshleman and Guo, 2014; Gerged et al , 2020; Ji et al , 2015; Nuskiya et al , 2021; Owusu et al , 2020; Zeng et al , 2020). Further to this, Sundgren and Svanstrom (2012) argue smaller audit firms receive more sanctions due to poorer audit quality, which coincides with the results above.…”
Section: Resultsmentioning
confidence: 99%
“…This paper seeks to contribute to the research on the trends and determinants of corporate social responsibility (CSR) disclosure in the context of developing countries and emerging economies (Petera et al 2019;Ahmad et al 2018;Matuszak et al, 2019;Sorour et al 2021;Khan et al, 2020;Nuskiya et al, 2021). CSR disclosure has become increasingly widespread (KPMG, 2020) from the perspective of more companies engaging with particular international reporting models/approaches (e.g., Global Reporting Initiative (GRI), Integrated Reporting (IR), Sustainable Development Goals Reporting, Sustainability Accounting Standards Board), and addressing a wider range of social and environmental themes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus their ability to effectively monitor the company management on behalf of the shareholders is limited. Previous empirical literature found that the busyness of directors can negatively affect a firm’s financial performance (Haniffa and Hudaib, 2006; Non and Franses,2007; Jackling and Johl, 2009; Niblaeus and Sellman, 2011; Cashman et al , 2012; Roudaki and Bhuiyan, 2015; Lusiana et al , 2020; Saleh et al , 2020; Latif et al , 2020; and Nuskiya et al , 2021), lower the sensitivity of CEO turnover to performance, manifest in a positive market reaction following the departure of a busy director (Fich and Shivdasani, 2006), lead to excess remuneration of CEOs (Core et al , 1999; Shivdasani and Yermack, 1999; Andres et al , 2013), lower board meeting attendance (Jiraporn et al , 2009) and increase the likelihood of committing accounting fraud (Beasley, 1996).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%